(3GdOQ GdefKhQ aj GdJaSjQ HGdeCKhQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdCfYGe s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI ghO s
(3GSJcedJ GdcJGHI ai gPG GdLRA ef hQbI (B249(3Edi BNQg HNW eZGjQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs